Management dynamics what color is your thinking hat? - Given, Karen L.; Primedia Workplace Learning (Carrollton, TX: PRIMEDIA Workplace Learning, 2000)
Explores effective use of'thinking hats' to enhance problem-solving brilliance, even when facing complex group dynamics of dealing with difficult people
Presenter, Karen L. Given ; host, Mike Russell
Keywords: Management; Interpersonal relations; Thinking; Group Processes